Disruption of genes involved in CORVET complex leads to enhanced secretion of heterologous carboxylesterase only in protease deficient Pichia pastoris. Issue 5 (30th March 2017) - Marsalek, Lukas; Gruber, Clemens; Altmann, Friedrich; Aleschko, Markus; Mattanovich, Diethard; Gasser, Brigitte; Puxbaum, Verena
Abstract: The methylotrophic yeast Pichia pastoris ( Komagataella spp.) is a popular microbial host for the production of recombinant proteins. Previous studies have shown that mis‐sorting to the vacuole can be a bottleneck during production of recombinant secretory proteins in yeast, however, no information was available for P. pastoris . In this work the authors have therefore generated vps (vacuolar protein sorting) mutant strains disrupted in genes involved in the CORVET (class C core vacuole/endosome tethering) complex at the early stages of endosomal sorting. Both Δ vps8 and Δ vps21 strains contained lower extracellular amounts of heterologous carboxylesterase (CES) compared to the control strain, which could be attributed to a high proteolytic activity present in the supernatants of CORVET engineered strains due to rerouting of vacuolar proteases. Serine proteases were identified to be responsible for this proteolytic degradation by liquid chromatography‐mass spectrometry and protease inhibitor assays. Deletion of the major cellular serine protease Prb1 in Δ vps8 and Δ vps21 strains did not only rescue the extracellular CES levels, but even outperformed the parental CES strain (56 and 80% higher yields, respectively). Further deletion of Ybr139W, another serine protease, did not show a further increase in secretion levels. Higher extracellular CES activity and low proteolytic activity were detected also in fed batch cultivation of Δ vps21 Δ prb1 strains, thus confirming that modifying early steps in the vacuolar pathway has a positive impact on heterologous protein secretion. Abstract : Improvement of recombinant protein secretion in the yeast Pichia pastoris is of great interest to enable more efficient production of enzymes and biopharmaceutical proteins. Vacuolar mis‐sorting was identified as one bottleneck, that could be overcome by disruption of genes involved in vacuolar transport. This approach was only leading to enhanced levels of secreted product, when vacuolar proteases were disrupted simultaneously.